Endoscopic Treatment of Pancreatic Fluid Collections (Journal of Medical Science, 2020)
Acute pancreatitis is frequently complicated by pancreatic fluid collections (PFCs)usually resolve spontaneously but some can mature forming large cysts filled with fluid or necrotic debris. Historically they have been surgical remov but with advancement of endoscopic procedures, endoscopic drainage has a safe firstline treatment of PFCs. Furthermore, the development of plastic stents and lumen apposing metal stents (LAMS) has replaced not only open surgery but also the percutaneous drainage due to adverse events. the LAMS has gained favor recently as large metaanalysis suggest their advantages over plastic stents in the treatment of PFCs, however data their use in the drainage of PFCs still scarce.